Genetic diversity of two perch Perca fluviatilis populations of the Latgale region (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Molecular markers based on retrotransposons possibility of integration into genomes of many organisms are commonly used for genetic analysis of different species. The aim of this study was to test possibility of use those markers in perch and detect genetic diversity of populations of two lakes of the Latgale region of Latvia: Cirišs and Sventes. The distance between the lakes is nearly 60 km, they belong to the same Daugava river basin but are different from ecological point of view. Forty two blood samples of Perca fluviatilis were collected altogether. Extracted DNA was analyzed using inter-PBS amplification technique with specifically selected retrotransposon-based primers and agarose gel electrophoresis. Data of genetic diversity of lakes were calculated by POPGENE and NTSYS software. In total, 127 loci were found in two populations, 81 of them were polymorphic. In spite of rather small distance between lakes Cirišs and Sventes, several differences in genetic variation of populations of two lakes were found. For example, the number of polymorphic loci in samples from Sventes lake was 61, but from Cirišs lake only 47. A unique allele was found in Lake Sventes. Genetic similarity and distance between populations of lakes Cirišs and Sventes was 0.9288 and 0.0739 respectively. Results proved that molecular markers based on retrotransposons PBS regions can be very useful to test genetic diversity of fish populations.